Clinical Features and Surgical Treatment of Primary Pulmonary Lymphoma: A Retrospective Study - Shen, Hui; Zhou, Yaodong (Frontiers in Oncology, 2022)
Abstract Background: Primary pulmonary lymphoma (PPL) is a rare clonal lymphoproliferative lung disease. The present study analyzes the clinical features, imaging data, pathologic characteristics, treatment and prognosis of PPL patients, with the aim to discuss the appropriate diagnosis and therapy of PPL patients in thoracic surgery. Methods: We performed a retrospective analysis on 36 patients with PPL confirmed by postoperative pathology between 2006 and 2020. We divided the patients into low-stage (IE) and high-stage (IIE) groups using modified Ann Arbor staging. The clinical manifestations, imaging findings, treatment modalities, and outcomes were evaluated. Results: The female to male ratio was 1.57:1 and the median age was 55 (31-69) years old. The majority of patients had stage IE disease (75%; 27of 36) and other 9 patients had stage IIE disease. Patients with advancing stage were more likely to have respiratory symptoms. The imaging findings presented as solid nodule or mass, pneumonia-like consolidative pattern, ground glass opacity and mix pattern. There were 31 cases of mucosa-associated lymphoid tissue lymphoma (MALT), 2 diffuse large B-cell lymphoma (DLBCL), 2 nodular sclerosing Hodgkin's lymphoma and 1 marginal zone B-cell lymphoma. Two patients were diagnosed with PPL and non-small cell lung cancer (NSCLC) synchronously (1 AIS and MIS, and 1 lung adenocarcinoma). All the patients received surgery. Nine patients received adjuvant therapy after surgery (5 radiotherapy, 2 chemotherapy and 2 chemoradiotherapy). Thirty-four patients provided a median follow-up time of 31 months (follow-up range: 7-152 months). Of the 34 patients, 1 patient died of liver metastases, and 1 patient died of intestinal metastases. Conclusions: Our retrospective analysis suggested most of PPL were indolent and had favorable prognosis. But the discrimination of PPL with other lung diseases was difficult. Preoperative biopsy and intraoperative frozen section examination might help the surgical choice. Limited lung resection was enough for peripherally localized PPL. Keywords: Primary pulmonary lymphoma, Biopsy, Pathology, Lung resection, Prognosis